2011
DOI: 10.3852/10-135
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium temperatumsp. nov. from maize, an emergent species closely related toFusarium subglutinans

Abstract: A large number of Fusarium isolates closely related to F. subglutinans were collected from maize in Belgium. We used a robust polyphasic approach to describe a new biological species, Fusarium temperatum, within the Gibberella fujikuroi species complex. F. temperatum can be distinguished from F. subglutinans and from other Fusarium species within the Gibberella fujikuroi species complex with AFLP fingerprint profile, differences in the translation elongation factor 1-α and β-tubulin DNA sequence and interspeci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 33 publications
10
85
0
2
Order By: Relevance
“…These are all mountain regions with a warm climate. Previous reports suggested that F. temperatum prefers warmer regions compared to F. subglutinans (Fumero et al, 2015;Moretti et al, 2008;Scauflaire et al, 2011). However, in this study, we also collected F. temperatum in Jilin, northern China, where the annual average temperatures are 3~5 °C and to our knowledge this is the coldest region where F. temperatum was isolated so far.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These are all mountain regions with a warm climate. Previous reports suggested that F. temperatum prefers warmer regions compared to F. subglutinans (Fumero et al, 2015;Moretti et al, 2008;Scauflaire et al, 2011). However, in this study, we also collected F. temperatum in Jilin, northern China, where the annual average temperatures are 3~5 °C and to our knowledge this is the coldest region where F. temperatum was isolated so far.…”
Section: Discussionmentioning
confidence: 84%
“…temperatum is a newly recorded species found first in 2011 in Belgium (Scauflaire et al, 2011). Recently, it was reported in many countries, including Spain (Varela et al, 2013), Poland (Czembor et al, 2014), Argentina (Fumero et al, 2015), and Korea (Shin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Schütt et al, 1998 Fusarium pseudocircinatum Fotso et al, 2002;Schütt et al, 1998Fusarium pseudonygamai Fotso et al, 2002Schütt et al, 1998 Hussein et al, 1991;Kriek et al, 1977;Marasas et al, 1986;Lew et al, 1996;Logrieco et al, 1993;Rabie et al, 1982;Schütt et al, 1998 Fusarium temperatum Scauflaire et al, 2011;Sewram et al, Ballester, A.R., Marcet-Houben, M., Levin, E., Sela, N., Selma-Lazaro, C., Carmona, L., Wisniewski, M., Droby, S., Gonzales-Candelas, L. …”
Section: Fusarium Pseudoanthophilumunclassified
“…subglutinans, called group 1 and group 2, with group 1 now described as a separate species, F. temperatum (Fumero et al, 2015, Scauflaire et al, 2011. According to Leslie and Summerell (2006), in the last 20 years at least four additional chainforming species have been described within the Section Liseola, including F. globosum, F. thapsinum, F. nisikadoi, and F. miscanthi, as well as some species that do not form chains (Leslie & Summerell, 2006, Rheeder et al, 1996, Klittich et al, 1997, Nirenberg & Aoki, 1997, Gams et al, 1999.…”
Section: Nebraska Was Described As F Moniliforme Sheldon and Was Incmentioning
confidence: 99%
“…Fusarium verticillioides and F. subglutinans are reported to colonise maize and sorghum (Leslie & Summerell, 2006, Yu et al, 2017. Fusarium temperatum is reported as a pathogen of maize (Scauflaire et al, 2011). Both F. thapsinum and F. andiyazi are pathogens of sorghum, although F. thapsinum is also thought to colonise banana, figs, maize, peanut and field soil (Leslie & Summerell, 2006, Klittich et al, 1997.…”
Section: Host Range Of Fusarium Moniliforme Sensu Latomentioning
confidence: 99%